2007
DOI: 10.1108/03699420710761816
|View full text |Cite
|
Sign up to set email alerts
|

Optimising synthesis conditions for long lasting SrAl2O4phosphor

Abstract: PurposeTo evaluate the effect of flux, activator and co‐activator on solid state synthesis of SrAl2O4: Eu2 + , Dy3 +  phosphor, where boric oxide, europium oxide and dispersium oxide were used, respectively.Design/methodology/approachTo optimise synthesis condition of long lasting phosphorescence SrAl2O4 phosphor, boric oxide was used as a flux. To improve relative intensity of SrAl2O4: Eu2 +  phosphor, the critical concentration of Eu2 +  was determined. The effect of various concentration of co‐activator on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It can be seen that the PL intensity of emission from Eu 2+ ions initially increases with the increase of dopant and co-dopant concentration. After it reaches the maximum value, a further increase in concentration makes the intensity decrease, because of the concentration quenching effect [21,72,80,81]. When considering the possible origin of the trap-ping centres, it can not be excluded that similar defects to those in α-Al2O3 could be present in the strontium aluminate -F centres ( , that is close to impossible to get rid of in the synthesis process, and intrinsic defects -F-centres and F2-centres luminescence.…”
Section: Intrinsic Defect Role In the Persistent Luminescence Mechanismmentioning
confidence: 99%
“…It can be seen that the PL intensity of emission from Eu 2+ ions initially increases with the increase of dopant and co-dopant concentration. After it reaches the maximum value, a further increase in concentration makes the intensity decrease, because of the concentration quenching effect [21,72,80,81]. When considering the possible origin of the trap-ping centres, it can not be excluded that similar defects to those in α-Al2O3 could be present in the strontium aluminate -F centres ( , that is close to impossible to get rid of in the synthesis process, and intrinsic defects -F-centres and F2-centres luminescence.…”
Section: Intrinsic Defect Role In the Persistent Luminescence Mechanismmentioning
confidence: 99%
“…[74,76,77] The green emission is characterized by a much higher quenching temperature of 440 K [4] and concentration quenching only sets in at Eu concentrations around 6%. [77][78][79] At low temperature, both emission bands have a comparable intensity in samples with a low activator concentration from which Poort et al [74] concluded that Eu 2+ is equally likely incorporated on both Sr sites. However, one should be careful when interpreting this statement as the intensity ratio of both emission bands is highly temperature-, concentration-, and excitation-wavelength-dependent.…”
Section: The Europium Activatormentioning
confidence: 98%
“…The green emission is characterized by a much higher quenching temperature of 440 K [ 4 ] and concentration quenching only sets in at Eu concentrations around 6%. [ 77–79 ] At low temperature, both emission bands have a comparable intensity in samples with a low activator concentration from which Poort et al. [ 74 ] concluded that Eu 2+ is equally likely incorporated on both Sr sites.…”
Section: Dopant Incorporation In Strontium Aluminatementioning
confidence: 99%
“…The alkaline earth aluminates based long afterglow phosphors as luminescent pigments are being actively explored nowadays because of their "glow-in-the-dark" and no radiation (Sharma et al, 2008;Li et al, 2008;Faridnia et al, 2007). When used in luminescent paint, it can be applied in emergency escape route guidance system, glow signs, display devices, toys, golf balls, etc.…”
Section: Introductionmentioning
confidence: 99%